2013
DOI: 10.1111/tid.12118
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose acyclovir prophylaxis for the prevention of herpes simplex virus disease after allogeneic hematopoietic stem cell transplantation

Abstract: ACV at 200 mg/day appeared to be effective for preventing HSV disease in the early phase after HSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…In previous studies, HSV disease after auto-and allo-HCT occurs in approximately 70-80 % of seropositive recipients without prophylaxis [1]. Low-dose acyclovir (200 mg/day) appeared to be effective for preventing HSV disease and was comparable to the Japanese standard dose (1000 mg/day) in the early phase after auto-HCT.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In previous studies, HSV disease after auto-and allo-HCT occurs in approximately 70-80 % of seropositive recipients without prophylaxis [1]. Low-dose acyclovir (200 mg/day) appeared to be effective for preventing HSV disease and was comparable to the Japanese standard dose (1000 mg/day) in the early phase after auto-HCT.…”
Section: Discussionmentioning
confidence: 85%
“…We previously reported that a low dose of acyclovir (200 mg/day) could reduce HSV and VZV disease in allogeneic recipients [1,10,11]. Therefore, in the present study, we retrospectively evaluated low-dose acyclovir prophylaxis for the prevention of HSV and VZV disease in auto-HCT patients.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…As prophylaxis against HSV infection and varicella zoster infection, acyclovir was given from days − 7 to 35, followed by long-term low-dose (200 mg/day) administration. 17,18 CMV antigenemia assay using C10/C11 antibody was performed at least once a week after engraftment and preemptive therapy with ganciclovir was started for high-risk patients. 19 Acute GVHD was graded as previously described.…”
Section: Other Transplantation Proceduresmentioning
confidence: 99%
“…Although such treatments may control the disease to some extent, they are still far away from satisfactory in curing the disease and controlling the spread of viruses [2]. In addition, long-term drug administration may result in side effects as well as drug tolerance [3,4,5,6,7]. Many investigators consider that the generation of specific active immune responses against viruses may be the most effective approach to control viral infections, therefore efforts are made in designing vaccines which can induce strong specific active antiviral immune responses [8,9,10].…”
Section: Introductionmentioning
confidence: 99%